1997
DOI: 10.1002/art.1780400711
|View full text |Cite
|
Sign up to set email alerts
|

The AIMS2‐SF. A short form of the arthritis impact measurement scales 2

Abstract: The AIMS2-SF is a shorter version of the AIMS2 (i.e., available in 2-page format) and has psychometric properties similar to those of the AIMS2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…These outcome measures were chosen as they form part of the core set of outcome measures in clinical trials of RA which were agreed upon by the OMERACT committee [11,21,22]. Secondary outcomes will be measured by the AIMS2-SF [23] and the Patient Knowledge Questionnaire [24].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcome measures were chosen as they form part of the core set of outcome measures in clinical trials of RA which were agreed upon by the OMERACT committee [11,21,22]. Secondary outcomes will be measured by the AIMS2-SF [23] and the Patient Knowledge Questionnaire [24].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Scores range from 1 (very uncertain) to 10 (very certain), with higher scores indicating higher self-efficacy [20]. However because in this study, function is being measured using Arthritis Impact Measurement Scales 2-SF (see AIMS2-SF below) described by Guillemin et al [23], only the pain and "other symptoms" subscales of the ASES will be used.…”
Section: Primary Outcome: Self Efficacymentioning
confidence: 99%
“…Twenty years later, these patient-based measures have been modified, re-scored, shortened, and, most importantly, consistently used in arthritis research and evaluation (10)(11)(12)(13)(14)(15). This continued focus on patient outcomes has well prepared both arthritis care providers and arthritis researchers to respond to the growing health care industry demand for outcomes evaluations and for practice decisions to be based on patient results.…”
Section: Patient-centered Outcomesmentioning
confidence: 99%
“…Previous research on outcome measures in hand OA has either focused on the examination of the psychometric properties of a specific PROM (16)(17)(18)(19)(20)(21)(22), their concurrent validity (23), or on comparisons with functional tests (24). With respect to comparability, a study has been conducted to examine the extent to which their content is comparable and revealed that most of the PROMs commonly used in hand OA capture similar aspects, in particular those associated with the Activity and Participation component of the International Classification of Functioning, Disability, and Health (ICF [25]).…”
Section: Introductionmentioning
confidence: 99%